Mosaic Tetrasomy 9p Associated With Inflammatory Bowel Disease. (25th April 2019) - Sifuentes-Dominguez, Luis; Starokadomskyy, Petro; Welch, Jacob; Gurram, Bhaskar; Park, Jason Y; Koduru, Prasad; Burstein, Ezra
Abstract: The genetic basis of inflammatory bowel disease remains to be elucidated completely. Here we report on a patient with inflammatory bowel disease who has mosaic tetrasomy of the short arm of chromosome 9, a genomic region that harbours the type I interferon gene cluster. We show that increased interferon activation is present in peripheral blood and intestinal tissue from this patient, similar to previous reports of autoinflammatory organ damage driven by interferon activation in other patients with this chromosomal abnormality. To our knowledge, this is the first case of tetrasomy 9p-associated interferonopathy driving intestinal inflammation and highlights the role that type-I interferon pathways can play in the pathogenesis of intestinal inflammation.